The Effect of Dupilumab on Intractable Chronic Rhinosinusitis with Nasal Polyps in Japan. (23rd November 2020) - Fujieda, Shigeharu; Matsune, Shoji; Takeno, Sachio; Asako, Mikiya; Takeuchi, Makiko; Fujita, Hiroyuki; Takahashi, Yoshinori; Amin, Nikhil; Deniz, Yamo; Rowe, Paul; Mannent, Leda
Abstract : Objectives/Hypothesis: Dupilumab, which blocks the shared receptor component for interleukin‐4 and interleukin‐13, reduced polyp size, sinus opacification, and symptom severity, and was well tolerated in patients with chronic rhinosinusitis with nasal polyps (CRSwNP) in the SINUS‐52 study (NCT02898454). We assessed dupilumab in patients enrolled at Japanese centers. Methods: Patients on a background of mometasone furoate nasal spray, received dupilumab 300 mg every 2 weeks (q2w) for 52 weeks (Arm A); dupilumab 300 mg q2w for 24 weeks, followed by every 4 weeks (q4w) for 28 weeks (Arm B); or placebo (Arm C). Co‐primary endpoints were week 24 nasal polyp score (NPS), nasal congestion (NC) score, and sinus Lund–Mackay CT (LMK‐CT) scores. Symptoms, sense of smell, health‐related quality of life, and safety were assessed during the 52‐week treatment period. Results: Of 49 patients enrolled in Japan, 45 completed the study. Week 24 least squares (LS) mean improvement versus placebo were as follows: NPS (Arm A: −3.1, P  < .0001; Arm B: −2.1, P = .0011); NC score (Arm A: −1.2, P  < .0001; Arm B: −0.9, P  < .0001); and LMK‐CT (Arm A: −5.1, P = .0005; Arm B: −2.8, P = .0425). The most common treatment‐emergent adverse event in dupilumab and placebo‐treated patients was nasopharyngitis. Conclusion: Dupilumab provided rapid, significant, and clinically meaningful improvements for patients with CRSwNP in Japan. Dupilumab was well tolerated, and safety and efficacy were consistent with the overall study population. Level of Evidence: 2 Laryngoscope, 131:E1770–E1777, 2021